Anti-atherogenic Effects of a New Thienylacylhydrazone Derivative, LASSBio-788, in Rats Fed a Hypercholesterolemic Diet - Nadia Alice Vieira da Motta; Arthur Eugen Kümmerle; Elisabeth Marostica; Caroline Fernandes dos Santos; Carlos Alberto Manssour Fraga; Eliezer Jesus Barreiro; Ana Luisa Palhares de Miranda; Fernanda Carla Ferreira de Brito (Elsevier, 2013)
The compound LASSBio-788 (N-Allyl (2-thienylidene) 3,4-methylenedioxybenzoylhydrazine) is a thienylacylhydrazone derivative shown to have antiplatelet, vasodilatory, and anti-inflammatory properties in vitro. We hypothesize that LASSBio-788 may exert beneficial effects on atherosclerosis. Male wistar rats were divided into 4 groups: Control group received standard rat chow, hypercholesterolemic group (HC) and HC+788 (compound LASSBio-788 group) received hypercholesterolemic diet for 45 days. HC+788 group received compound LASSBio-788 (100 μmol/kg) once daily in the last 15 days. LASSBio-788 reduced the levels of total cholesterol (109.1 ± 4.3 vs. 361.0 ± 12.8 mg/dl), triglycerides (66.1 ± 1.1 vs. 186.9 ± 17.7 mg/dl), LDLc (63.2 ± 6.1 vs. 330.9 ± 9.7 mg/dl), VLDLc (9.8 ± 1.1 vs. 45.0 ± 4.6 mg/dl) and malondialdehyde (4.8 ± 0.3 vs. 9.4 ± 0.5 nmol/ml) compared to the HC group. LASSBio-788 presented antiplatelet properties and decreased inflammatory markers levels. LASSBio-788 promoted a decrease in contractile response to phenylephrine and an improvement in endothelium-dependent vasorelaxant response by increasing two-fold the expression of nitric oxide synthase (eNOS). Our results suggest that the compound LASSBio-788 represents a new multi-targeted drug candidate for the treatment of atherosclerosis. Keywords:: atherosclerosis, anti-platelet, anti-inflammatory, lipid-lowering, thienylacylhydrazone derivative